Analysis of Current Urban Forest Governance in the City of Zagreb : doktorska disertacija - Krajter Ostoić, Silvija (Array, 2013)
"Urban forests and green space provide many benefits and are important for quality of life of urban population. Urban forest governance should enable these goals. However, it is rarely subject of comprehensive scientific inquiry. Effect of discourses on environmental governance has been widely documented, but it is not the case for urban forest governance. Goals of this dissertation are several. First global scientific discourses on urban forestry and governance will be identified and described based on literature review. Next local urban forest governance arrangement in the City of Zagreb will be explained. Furthermore, governance performance assessment according to interviewees will be addressed. In the end connection between global discourses and local practice presented by the case study of urban forest governance in the City of Zagreb will be discussed."